Algorithm for the cliticization of context dependent pronouns in Pashto language - Din, Azizud (2013)
The replacement of strong pronouns with counterpart weak pronouns (Citics) is an important task in the translation of Pashto into other languages by computer before anaphora resolution can take place. Repetition of proper nouns and common nouns is not a good way in a language.Instead of it, pronouns are used in most languages but in Pashto language weak pronouns are mostly used in context dependent text.Especially in poetry often clitics are used instead of strong pronouns.The presence of clitics and strong pronouns at the same time in Pashto language complicates anaphora resolution. Replacing strong pronouns with clitics makes the text very simple and efficient.In Pashto, some pronouns are context free and some are context dependent.Context free pronouns can be replaced with clitics using simple rules that encompass a single sentence in which the pronoun itself occurs.Replacement of context dependent strong pronouns with corresponding clitics involves syntactic agreement across single or multiple clauses. In this paper, an algorithm is presented for the cliticization of context dependent strong pronouns which backtracks to previous adjacent clause(s) to replace context dependent strong pronoun with clitics using syntactic constraints.